T Lymphocytes, Multi-Omic Interactions and Bronchopulmonary Dysplasia - Toldi, Gergely; Hummler, Helmut; Pillay, Thillagavathie (Frontiers in Pediatrics, 2021)
Bronchopulmonary dysplasia (BPD) remains a significant clinical challenge in neonatal medicine. BPD is clearly a multifactorial disease with numerous antenatal and postnatal components influencing lung development. Extremely immature infants are born in the late canalicular or early saccular stage and usually receive intensive care until the early alveolar stage of lung development, resulting in varying magnitudes of impairment of alveolar septation, lung fibrosis, and abnormal vascular development. The interactions between T lymphocytes, the genome and the epigenome, the microbiome and the metabolome, as well as nutrition and therapeutic interventions such as the exposure to oxygen, volutrauma, antibiotics, corticosteroids, caffeine and omeprazole, play an important role in pathogenesis and disease progression. While our general understanding of these interactions thanks to basic research is improving, this knowledge is yet to be translated into comprehensive prevention and clinical management strategies for the benefit of preterm infants developing BPD and later during infancy and childhood suffering from the disease itself and its sequelae. In this review, we summarise existing evidence on the interplay between T lymphocytes, lung multi-omics and currently used therapeutic interventions in BPD, and highlight avenues for potential future immunology related research in the field.